Planos de texto e sequências textuais descritivas no documento de Pastoral Escolar da Sagrado Rede de Educação - Oliveira, Vânia Cristina de (2015)
This work, whose theme refers to the text plans and descriptive textual sequences in the documents of the School Pastoral at the Sacred Education Network, is part of the line of Research on Text and Speech both in the oral and written forms. From the questions of how to organize the text plans and descriptive textual sequences in some texts of the School Pastoral document, and how they contribute to understanding the educational mission of the Institution, the goals were set: to identify, to describe, to analyze and to discuss the descriptive textual sequences and the text plans in the school pastoral document and to reflect on the use of the descriptive in it, to understand the educational mission of the Institution. Based on Textual Linguistics and, more specifically, in Textual Analysis of Discourses, this research was supported in studies of text concepts, types and textual genres, text plans, textual sequences and the descriptive: categories and sequences. The selected scholars for the research theoretical grounds were: Adam (1992; 2011); Marquesi (2004; 2012; 2013; 2014; 2014th), Koch (2011; 2013; 2014), Travaglia (2007, 2014, forthcoming), Marcuschi (2008), Coutinho (2003), Cabral (2013), Bonini (2005 ) and Bazerman (2011). The corpus is made up of five texts selected from the Educational Pastoral Plan of the Sacred Education Network. The results obtained in the analysis reveal striking qualities of the descriptive in the selected texts of the school pastoral. Through the descriptive, we could name, place and qualify the studied subjects and verify a close correspondence in relation to the educational mission of the Sacred Education Network